Mediation and structure in the Coplas by Manrique (Letras, 2019)
In this article we analyse the tripartite structure in the Coplas a la muerte de su padre by Jorge Manrique, in correlation to other triadic patterns of the poem by which themes, symbols, and rhetoric devices are organized. The third part fulfills a function of union and mediation (not synthesis nor overcoming) of the two previous parts, according to the theological model of Christ, but also according to the anthropological and social model of Chivalry.
Keywords: Manrique; Coplas; Structure; Tripartition; Mediation